Introduction - Hipólito, Rodrigo (Revista do Colóquio, 2025)
The twenty-sixth edition of the Colloquium Journal brings together seventeen contributions that address fundamental issues in contemporary art, from gender and coloniality issues to reflections on memory, constructive tradition, and art education. The works gathered here demonstrate the vitality of art research in Brazil and reveal how artistic production and its critical investigation remain spaces of resistance, questioning, and social transformation.
Keywords: presentation; edition; introduction